Institutionalizing Health Technology Assessment in South Africa-An Opportunity in National Health Insurance - Janine Jugathpal; Andrew Parrish; Khadija Jamaloodien; Mark Blecher; Jonatan Daven (Taylor & Francis Group, 2023)
While South Africa has some experience in various forms of health technology assessment (HTA), it is currently fragmented across numerous players. Additionally, there is a lack of systematic and consistently applied HTA processes that inform priority-setting and budget allocations. To address this, the country is journeying toward more institutionalized use of HTA. This will begin with the establishment of a Ministerial Advisory Committee on HTA for National Health Insurance (NHI) and will gradually embed HTA processes in decision-making. The goal is to create an independent HTA agency. Although these reforms will be intrinsically linked to the wider health financing reforms envisaged under NHI, such as formulating the benefits package, they will also assist in strengthening South Africa's health system. As a country facing a highly constrained fiscal environment, with limited space for additional funding for the health sector, evidence-based priority-setting will be critical to ensure that value for money is achieved in the government's investments in health care services in NHI.